SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAGANG PADA PT TASLY WORLD INDONESIA CABANG BANDUNG - Hery Dwi Yulianto; Sifa Fauziah; Ony Widilestariningtyas (Labkat Press KA FTIK UNIKOM, 2012)
PT Tasly World Indonesia Branch Bandung is addressed in Jl. Abdul Rachman Saleh 9 City Square A-3 Bandung. At the time of recording supplies, PT Tasly World Indonesia Branch Bandung is already using the computer by using Microsoft Office Excel 2003, which is often in error recording. On the problems the writer took the title